Improving human resource management system through the formation of professional communicative competence - S. A. Sukhenko (Путеводитель предпринимателя, 2020)
The article examines the stages of formation of the competence approach in labor economics. The analysis of the concepts of «competence» and «competence» in the context of the theory of human resource management. The structure of professional competence of the manager. Presented component model structure of communicative competence. The urgency of the formation of professional communicative competence as a factor in improving human resource management system.